A generalized pseudo-rigid-body PPRR model for both straight and circular beams in compliant mechanisms. (December 2020) - Xu, Hao; Gan, Jinqiang; Zhang, Xianmin
Highlights: A generalized pseudo-rigid-body PPRR model is developed. The parameters of the developed model are identified by PSO algorithm. The model has higher accuracy than the PRB 2R, 3R and RRHR model. The model can be applied in modeling of both straight and circular beams. Abstract: The pseudo-rigid-body (PRB) models have been widely applied for modeling of straight beams in compliant mechanisms. In this paper, a generalized PRB PPRR model with two mutually perpendicular linear springs is established for both straight and circular beams in compliant mechanisms. In the developed model, the static equations of the deflected beams are derived from Bernoulli's equation. The characteristic parameters of the developed model are identified by the reasonably organized particle swarm optimization (PSO) algorithm. A simulation experiment of tip locus of a circular beam is conducted to evaluate the developed model. The simulation results show the developed model has higher accuracy than the PRB 2R, 3R, and RRHR model. In addition, two numerical examples are further implemented to demonstrate the effectiveness of the developed model.